Психічні стани працівників опен спейс в умовах самоізоляції - Жданова, І. В.; Zhdanova, I. V.; ORCID: http://orcid.org/0000-0002-6361-3029; Шахова, О. Г.; Shakhova, O. H.; ORCID: http://orcid.org/0000-0002-7860-6972; Гайдук, Н. С.; Haiduk, N. S. (Габітус. - 2022. - Вип. 33. - С. 185-189, 2022)
Представлено результати дослідження психічних станів, які переживали працівники опенс спейс в умовах самоізоляції у період пандемії COVID-19. Визначено стан розробки проблеми психічних станів особистості під час епідеміологічних спалахів, встановлено наявність «другої епідемії» психологічних наслідків COVID-19 у вигляді негативних психічних станів та підвищеного ризику психічних розладів. Окреслено негативну роль соціальної ізоляції особистості, підкреслено вплив вимушеної самоізоляції на психічні стати різних категорій населення, зокрема працівників опен спейс.

The article presents the results of a study of mental states experienced by open space workers in self-isolation during the COVID-19 pandemic. Based on the theoretical analysis of the literature, the state of development of the problem of mental states of the individual during epidemic outbreaks was determined, the presence of the “second epidemic” of negative psychological consequences of COVID-19 in the form of negative mental states and increased risk of mental disorders, study of the impact of forced self-isolation on the mental health of various categories of the population, in particular, open space workers. The study, which was conducted online in April 2020 during the lockdown, used the following psycho-diagnostic methodologies: questionnaire “Personal Issues Inventory” A. Jersild, methodology for the differentiated assessment of states of reduced performance, author's questionnaire (N.S. Haiduk). Respondents were 40 female employees of one of the international companies who work in an open office – open space, and who worked in isolation, remotely during the lockdown. The results of the study indicate a loss of sense of security, the presence of states of nervous tension and uncertainty, feelings of hopelessness, isolation, loneliness, and a clear need for the vast majority of respondents to communicate. Workers under the age of 30 were more likely to experience loneliness and isolation, uncertainty about the future, occupational stress, and the risk lose their ability to work in conditions of forced self-isolation. For middle-aged respondents, states of helplessness, loss of security, increased irritability and anger, and professional fatigue were more typical. Based on the results obtained, conclusions were drawn about the dominant mental states of open space workers in conditions of forced self-isolation and the importance of their psychological education.

Представлены результаты исследования психических состояний, которые переживали работники опенс спейс в условиях самоизоляции в период пандемии COVID-19. Определено состояние разработки проблемы психических состояний личности во время эпидемиологических вспышек, установлено наличие «второй эпидемии» психологических последствий COVID-19 посредством негативных психических состояний и повышенного риска психических расстройств. Обозначена негативная роль социальной изоляции личности, подчеркнуто влияние вынужденной самоизоляции на психические стать разных категорий населения, в том числе работников опен спейс.
Mental states of open space workers in conditions of self-isolation
Жданова, І. В. Психічні стани працівників опен спейс в умовах самоізоляції / Жданова І. В., Шахова О. Г., Гайдук Н. С.// Габітус. - 2022. - Вип. 33. - С. 185-189. - DOI https://doi.org/10.32843/2663-5208. 2022.33.33.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; психічні стани; mental states; психические состояния; особистість; personality; личность; самоізоляція; self isolation; самоизоляция; працівники офісів опен спейс; office workers open space; работники офисов опен спейс; пандемія COVID-19; COVID-19 pandemic; пандемия COVID-19